Linguistic violence between student’s in preparatory school in Zakho city - Abdullah, Abdulsalam N.; Saleh, Huda I. (Humanities Journal of University of Zakho, 2017)
Linguistic violence in school consists of number of wrong speech between students themselves or between teacher and students. As a result, it may be lead to unexpected behavior. This research attempt to find the level of linguistic violence between student’s in preparatory school in Zakho city. In addition, to determine the factor and causes that led to this phenomenon. Moreover, the approach that determines the solutions and how to protect against this phenomenon. For a purpose, lower linguistic violence indoor school. This research includes tow hypotheses. The first one is about the existence of linguistic violence between student’s speech. The second hypothesis is about the relation between linguistic violence and gender. Collection of data were based on the distribution of questioner over students, and then collect and analysis them by (SPSS) program. Number of research sample was (253) students from male and female. The following statistical instrument were used 1/ one-way ANOVA 2/ t-test and 3/Likert measurement. The practical data from questioner are inserted to SPSS program. The data are analyzed statistically. The first hypothesis is accepted and one pivot from the second hypothesis is also accepted. And all other hypothesis is rejected at confidence level 0.05.